Artificial Intelligence in Enhancing Ecology Essays: A Study in a Brazilian High School - da Silva Neto, Sebastião Luiz (2024)
In recent years, technological advances have significantly transformed educational practices. The development and adoption of Artificial Intelligence (AI) chatbots in education have recently generated widespread interest from teachers and students. In this context, this research aimed to evaluate the potential of AI resources as an auxiliary instrument in improving dissertation-argumentative essays prepared by second-year high school students on Ecology. This is qualitative research, specifically of the action research type, conducted through three stages. The results show that chatbots can be used as complementary resources in the classroom, in addition to having the potential to optimize the construction of knowledge. Finally, it was observed that chatbots were able to facilitate the application of content and make assessments more engaging and productive.